Peran Duta Literasi, Digitalisasi Koleksi, dan Integrasi Layanan Perpustakaan terhadap Peningkatan Literasi - Fadhilah Nurinsani Hidayat; Perdana, Purnama Rika; Rusdan Kamil; Siti Supiah (Journal of Mandalika Literature, 2025)
The campus library is one of the parties responsible for community literacy. Article 4 of Republic of Indonesia Law Number 43 of 2007 states that libraries have to increase the love of reading and expanding knowledge. Library literacy is a sense of familiarity with the resources, services, and organization of library collections. This research focuses on three things: (1) What is the role of literacy ambassadors in increasing community literacy? (2) What is the process of digitizing collections at UIN Banten to increase public literacy? And (3) How are campus library services integrated into increasing community literacy? This research uses qualitative methods focused on elaborating research problem points (Huyler & McGill, 2019). The results of this research are formulated as follows: 1. Literacy Ambassadors are tasked with increasing student literacy awareness, promoting library services, and building a literacy community, 2. Digitalization in the UIN SMH Banten Library prioritizes thesis collections that can be accessed by anyone, 3. Integration of Central and Faculty Library services is carried out by forming a team, training the library staff including involving Literacy Ambassadors, analysing library needs, integrating collection catalogues, establishing policies, and conducting outreach